Kermes oak shrubland resource availability and grazing responses by goats as influenced by stocking rate and grazing system - Tsiouvaras C.N.; Nastis A.S.; Papachristou T.G.; Platis P.D.; Yiakoulaki M. (Systèmes d'élevage et gestion de l'espace en montagnes et collines méditerranéennes, 1999)
Seasonal effects of three stocking rates on resource availability and intake of goats were evaluated in a kermes oak (Quercus coccifera L.) shrubland in Greece from 1991 to 1994. Stocking rates were: moderate (MSR: 1 goat/ha/y), heavy (HSR: 2 goats/ha/y) and very heavy (VHSR: 4 goats/ha/y). In an adjacent kermes oak shrubland the effects of a continuous and a rotational grazing system on forage conditions and animal performance were studied from 1992 to 1994. The stocking rate was set at 1.3 goats/ha/y. Vegetation cover (62 per cent), forage production (1413 kg/ha) and goat liveweight gain (minus 2.3 kg/goat) were significantly lower and bare soil plus litter higher (38 per cent) in the VHSR compared to MSR (85 per cent, 2905 kg/ha, 1.0 kg/goat and 15 per cent) and HSR (80 per cent, 2067 kg/ha, 0.5 kg/goat and 20 per cent) while there were no significant differences (P less or equal to 0.05) between MSR and HSR in all parameters but the total forage production. The goats' forage intake was lower in HSR and VHSR (32.9 g/kg BW0.75 and 33.3 g/kg BW0.75 respectively) compared to MSR (46.3 g/kg BW0.75) only during the winter. As far as the grazing system is concerned, the bare soil plus litter was decreased by 67 per cent and 35 per cent in the rotational and the continuous grazing respectively from 1992 to 1994, while the average forage production, the shoot number from regrowth and the shoot length were higher in the rotational (3018.0 kg/ha, 35.5 n/m2 and 3.0 cm/shoot respectively) compared to continuous grazing (2413.3 kg/ha, 31.4 n/m2 and 2.0 cm/shoot respectively). Finally, goats in the rotational grazing gained significantly more weight (1.93 kg/animal) compared to continuous grazing (minus 0.60 kg/animal).